If you solve by completing the squre, fill in the blanks.

2x^2 + 14x + 1 = 0

x^2 +7x + (blank) = -1/2 + (blank) *Blank 1, both are the same answer.

(x + 7/2)^2 = (blank) *Blank 2

x + 7/2 = +- sqrt(47)/2

x = -7/2 +- sqrt(47)/2

Answer Blank 1 and 2.

### 1 Answer | Add Yours

`2x^2+14x+1 = 0`

`x^2+7x+1/2 = 0`

`x^2+7x = -1/2`

`x^2+7x+(7/2)^2 = -1/2+(7/2)^2`

*So blank 1 = (7/2)^2 = 49/4*

`(x+7/2)^2 = -1/2+49/4`

`(x+7/2)^2 = 47/4`

`(x+7/2)^2 = +-sqrt(47)/2`

*So blank 2 = 47/4*

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes